Lifestyle assessment in young adults with ischemic stroke: One cross-sectional study in Iran - Arezoo Chouhdari (Wolters Kluwer Medknow Publications, 2021)
Background and Aim: Lifestyle changes are associated with an increased incidence of stroke especially in young adults. The purpose of this study was to investigate the lifestyle of ischemic stroke cases under the age of 50 years. Methods: This descriptive cross-sectional study was conducted on young adults with ischemic stroke who were admitted to some hospitals, Tehran, Iran between 2018 and 2019. Total lifestyle information collected in the form then was compared in males and females. Results: Totally 11% ischemic stroke was under age 50 years. 60.7% of young adult patients were men. There was significant difference between body mass index (BMI) (P = 0.03), type of job (P = 0.04), physical activity (P = 0.02), fruit and vegetables consumption, and gender of patients (P = 0.02). Conclusion: According to the association between inappropriate lifestyle and ischemic stroke in young adults, it is recommended to set preventive medicine and health promotion units with insurance coverage in all clinics for risk assessment of stroke in healthy general population specialty young adults.